Improving patient care at a multi-speciality hospital using lean six sigma. Issue 12 (10th September 2022) - Persis, D. Jinil; S., Anjali; Sunder M, Vijaya; G, Rejikumar; Sreedharan, V. Raja; Saikouk, Tarik
Abstract: Healthcare has been an important necessity globally. Healthcare organizations have realized the importance of continuous improvement practices like lean six sigma (LSS). In this study, the authors examine the impact of LSS to improve patient care. A case study approach was selected to evaluate the operational excellence of a multi-speciality hospital. The data collected was analyzed using a novel approach, viz. SDMMAICS. The analysis helped to remove the bottlenecks and improve key performance metrics such as patient turnaround time (TAT), workforce utilization, and organizational profits contributing to the operational excellence of the cardiology department. The study reduced staff and teams' idle time with an annual saving of 3, 44, 3658 INR (44, 000 USD). This study helps both research scholars and practitioners to understand how LSS helps transform healthcare organizations.